RESULTS OF TECHNICAL INSPECTION OF THE MAIN MEDICAL BUILDING (A-2 BUILDING) AND THE GARAGE (B BUILDING) IN THE CITY OF LVIV - Burchenia С.; Vikhot С. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
To ensure the reliability of a real estate object, it is essential to conduct a thorough technical inspection. Building inspection involves assessing the structural system, engineering systems, and surrounding environment to detect potential flaws, prevent structural failure, and ensure necessary repairs are completed. This significantly extends the life of the object. The article presents the results of the inspection of the main structural building elements. The foundations have a physical depreciation of 21–40 %, but their technical condition is satisfactory (technical condition category «2»). The paving's technical condition is non-serviceable for proper exploitation (technical condition category «3»). The walls and partitions have a physical depreciation of 31–40 %, but their technical condition is satisfactory (technical condition category «2»). The floors have a physical depreciation of 41–60 %, and their condition is non-serviceable for proper exploitation (technical condition category «3»). The same applies to the floors with physical depreciation of 61–80 %. The engineering networks have a physical depreciation of 61–80 %, and their technical condition is non-serviceable for proper exploitation (technical condition category «3»). Based on the inspection and analysis of the technical conditions of the main medical building (A-2 building), garage (B building), it is established that their general technical conditions classify as technical state «3» (non-serviceable for proper exploitation).